Spectroscopic and Fluorometric Determination of Cinnarizine and Dipyridamole in Pharmaceutical Tablets Using Eosin Y Dye - Zeina Al - Abdali; Elham Saleh (College of Education for Pure Sciences, 2013)
ABSTRACT Spectrophotometric and spectrofluorimetric methods were developed for the determination of cinnarizine and dipyridamole. The spectrophotometric method is based on the formation of ion pair complex  between the studied drugs and eosin Y which shows maximum absorbance at 550 nm in the phthalate buffer (pH3.5) for cinnarazine and 547 nm in citrate buffer (pH3) for dipyridamole. Beerʼs law is obeyed in the concentration ranges of 0.1-8 and  0.1-7 µg/ml with molar absorbitivity values of 4.65×104 and 4.90×104 L.mol-1.cm-1 for cinnarizine and dipyridamole respectively. The spectroflurimetric method is based on the quantitative quenching effect of cinnarizine and dipyridamole on the native fluorescence of eosin Y. The quenching of the fluorescence of eosin Y was measured at 553 nm after excitation at 350 nm. The fluorescence-concentration plot is rectilinear over the ranges of 0.05-5.2 and 0.1-5.0 μg/ml for cinnarizine and dipyridamole respectively. The two proposed methods were successfully applied for the determination of drugs in pharmaceuticals preparations.